2004
DOI: 10.1103/physreve.70.026604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dynamics of a blue-violetInxGa1xNlaser with a saturable absorber

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The numerical simulation of a reference single QW (SQW) laser structure (Figure 3) is considered to study the non-c-axis-oriented InGaN blue laser optoelectronic performance [17]. This laser structure has been developed by Sharp Corporation at Devices Technology Research Laboratories located in Nara, Japan.…”
Section: Laser Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The numerical simulation of a reference single QW (SQW) laser structure (Figure 3) is considered to study the non-c-axis-oriented InGaN blue laser optoelectronic performance [17]. This laser structure has been developed by Sharp Corporation at Devices Technology Research Laboratories located in Nara, Japan.…”
Section: Laser Structurementioning
confidence: 99%
“…The structure is also composed of n and p-type InGaN buffer layer in order to maintain low spontaneous emission, n and p-type Al 0.1 Ga 0.9 N top/bottom cladding layer to confine carrier spillover, n and p-type GaN top/bottom optical guiding layer and a p-type Al 0.3 Ga 0.7 N evaporation-prevention layer. An oxide aperture is deposited above the upper AlGaN layer for current and index confinement [17]. In the proposed laser system, the active region material has (hkil) orientation, and all other layers are in (0001) orientation.…”
Section: Laser Structurementioning
confidence: 99%
“…Earlier studies concentrated on self-pulsation for applications in optical storage systems since this approach can reduce the optical feedback noise [1--14]. Several pulse generation techniques exist, including gain-switching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], self-pulsating [18][19][20], mode-locking [7,17,21], and superradiance [22]. Kono et al demonstrated the first gain-switching (GS) operation of a GaN-based LD, producing a peak power of 12 W and 10 W with a pulse duration of 10 ps at 405 nm [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Other laser architectures with saturable absorber for SSP have also been proposed. 5,6) An additional advantage to realizing optical clock sources with semiconductor lasers is that its pulsation frequency can be tuned electrically. Some theoretical models have been proposed to describe the SSP mechanisms.…”
Section: Introductionmentioning
confidence: 99%